Last Men Standing - Djurkovic, Sasha M. (United Kingdom : National Film ; Television School Beaconsfield Studios, 2005)
Ten years after the mass pit closures of 1984 the miners of the Tower Colliery pooled their severance pay and bought their own pit. They believed they were securing the future of their community. What will happen to the children and grandchildren of the 'last men standing'?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films